An moving discussion, an important move: : notes on the antagonism around the figure of the cangaceiro - Alves, Antonio Robson de Oliveira (Em Perspectiva, 2023)
A theme that received and still receives a lot of attention within the field of banditry studies it is the cangaço and this has as its basic figure the cangaceiro. Thus, this text aims to review the discussions that have been formulated over the years about the cangaceiro, his naked actions show diffuse and dissenting views, as on the one hand he is regarded as a hero, and on the other as a villain, a bandit and a thug. With that, we will go through these discussions aiming to broaden the theoretical north and map the allegations made so far, dialoguing with authors and areas of human knowledge and seeking to highlight the importance of studies on banditry in the Northeast region of Brazil.